Improving US animal disease preparedness: animal disease traceability and biosecurity with an emphasis on Foot-and-Mouth Disease - Smith, MaRyka Renae (My University, 2026)
Foot-and-Mouth Disease (FMD) is a highly contagious, transmissible, viral disease of cloven-hooved livestock. The clinical signs in animals infected with FMD are vesicular lesions around the hooves, teats, and mouth that develop 2 to 14 days after infection. Animals may be infectious to others in as few as 2-3 days after infection, during the preclinical phase. Infected animals often experience production losses due to the pain associated with the clinical signs. Outbreaks of FMD cause economic losses for the country or region affected due to depopulation, trade losses, outbreak control costs, and disruption to business continuity. The United State (US) has not had an outbreak of FMD since 1929, but the ongoing global movement of humans, animals, and animal products, means that the threat of FMD remains constant. The virus's rapid spread and the potential for economic devastation highlight the need for research into FMD response planning. The current US FMD response is described in the Foot-and-Mouth Disease Response Plan (“The Red Book”). The Red Book is designed to swiftly control and eradicate an outbreak in order to return the US to FMD freedom as quickly as possible. A potential cost of strict disease control measures is loss of business continuity on farms that are not infected. To balance this need for disease control and business continuity, the “Secure Food Supply” plans have been developed to assist producers with biosecurity and contingency planning. Both the Red Book and Secure Food Supply plans recommend best practices for disease control. However, there is a gap in empirical data supporting the efficacy of many field biosecurity practices. Effective disease traceability can also aid outbreak control and business continuity by identifying dangerous contacts and enabling the accurate implementation of surveillance and quarantine. Currently, the US does not have complete digital traceability of susceptible livestock. Producers are not legally required to apply electronic identification (EID) to all animals and not all animal movements are required to be reported. This can lead to delays or failure in identifying all diseased and at-risk animals in a disease investigation, which could ultimately allow the continued transmission of disease. There have been recent advances in the use of electronic identification (EID) and digital movement reporting, but quantitative data on the impacts of improving digital traceability are limited. To address the biosecurity knowledge gap, a scoping review was conducted on the implementation of a biosecurity measures for FMD mitigation at the farm level. A systematic search of 4 databases identified 3,153 unique records. The inclusion criteria for further review required reports to be original, peer-reviewed research, published in English, to describe or evaluate a biosecurity measure applied at the farm level to mitigate FMD risk, and to include at least one of the US domestic, FMD-susceptible livestock species. After abstract and full-text evaluation, 22 reports were included in the review. The reports included 2 experimental studies and 20 field reports. The experimental studies showed that hand washing, showering, and changing outerwear were more effective than no interventions. The field studies reported many measures, but none were consistently reported as effective for FMD mitigation across multiple reports. This scoping review highlighted the insufficiency of the published literature on FMD field biosecurity measures and the difficulty of acquiring biosecurity data in the field setting. The findings of this review can be used to shape future research questions in biosecurity field studies and to improve the reporting of biosecurity measure literature. Improving biosecurity knowledge can help producers and animal health officials develop FMD response plans that are effective for risk mitigation, economically responsible, and feasible to implement. To address gaps in animal disease traceability, we assessed the impacts of EID and digital tracing using simulated FMD outbreaks in the US. The program InterSpread Plus (ISP) was used to simulate FMD outbreaks from feedlot, cow-calf, and dairy farms across multiple locations in the US. The outbreaks were defined by their starting location and farm type, the level of tracing, and the day the first farm was detected. The tracing levels represented the current tracing speed and accuracy, a partial implementation of EID (approx. 70% success), and an ideal implementation of EID tracing (99% success). Each scenario was tested with 100 simulated outbreaks. The primary outcome of interest in simulated outbreaks was the size of the outbreak, measured as the number of infected premises (IPs). The day the outbreak was detected was highly influential in determining outbreak size. Outbreaks detected on days 8 and 14 were smaller in size than those detected on day 21. Outbreaks detected on day 21 had the largest reduction in the number of IPs from the current tracing to the improved tracing scenarios. Improved tracing suggested a decreased likelihood for the largest and most devastating outbreaks across all introduction locations. These results support the need for improved traceability to aid in controlling an FMD outbreak. The simulation of FMD outbreaks and the improvement in traceability focused on the speed and accuracy of completing a trace, but did not address the proportion of farms that must use the tracing technology to achieve those metrics. The final project in this dissertation addressed this gap by applying tagging and digital reporting to simulated movement networks. The ISP FMD outbreak model was reconfigured to remove outbreak controls to generate a movement network of cattle. Cattle move between farms, markets, feedlots, processors, and other cattle premises. The farms in the simulated network were then randomly assigned as tagging and reporting farms at varying rates. The traceability scenarios were developed to represent the current status of EID and digital reporting, and were progressively improved toward a hypothesized ideal EID utilization. If the source farm of a movement originated tagged and the destination farm reported it was deemed “traceable.” The traceable movement networks were then subjected to contact tracing to assess whether contacts from randomly selected farms could be located. The simulation of the current level of EID and digital tracing had near-zero success for contact tracing. The number of traceable contacts did not exceed 50% for cow-calf farms until 75% of all farms tagged and reported movements. In the highest-traceability scenario, 75% of farms were tagged, and 90% reported, resulting in traceability of 60% of cow-calf contacts and over 80% of market contacts. Additional analysis showed that the increase in tagging without an increase in digital reporting did not improve traceability. These results highlight the need for substantial improvements in EID tag utilization and in digital reporting database infrastructure. The combination of these projects adds to the body of literature that animal health officials, livestock producers, and veterinarians can use when preparing for and responding to a potential introduction of FMD. These results could be extrapolated to control many other livestock diseases and used to develop novel research topics for disease preparation.
Keywords: Epidemiology; Foot-and-Mouth Disease; Modelling; Traceability; Biosecurity; Cattle